(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The results of studying the waterretaining capacity of leaves of 14 pear varieties from the collection of the Scientific Research Institute Botanical Garden named after V.I. E. Gareeva NAS KR. Varieties with high waterretaining capacity have been selected.